A Phase I, First-in-Human Study of GSK2849330, an Anti-HER3 Monoclonal Antibody, in HER3-Expressing Solid Tumors. (21st July 2021) - Gan, Hui K.; Millward, Michael; Jalving, Mathilde; Garrido-Laguna, Ignacio; Lickliter, Jason D.; Schellens, Jan H.M.; Lolkema, Martijn P.; Van Herpen, Carla L.M.; Hug, Bruce; Tang, Lihua; O'Connor-Semmes, Robin; Gagnon, Robert; et al.
Abstract: Background: GSK2849330, an anti-HER3 monoclonal antibody that blocks HER3/Neuregulin 1 (NRG1) signaling in cancer cells, is engineered for enhanced antibody-dependent cellular cytotoxicity and complement-dependent cytotoxicity. This phase I, first-in-human, open-label study assessed the safety, pharmacokinetics (PK), pharmacodynamics, and preliminary activity of GSK2849330 in patients with HER3-expressing advanced solid tumors. Patients and Methods: Patients with various tumor types were prospectively selected for HER3 expression by immunohistochemistry; a subset was also screened for NRG1 mRNA expression. In the dose-escalation phase, patients received GSK2849330 1.4–30 mg/kg every 2 weeks, or 3 mg/kg or 30 mg/kg weekly, intravenously (IV). In the dose-expansion phase, patients received 30 mg/kg GSK2849330 IV weekly. Results: Twenty-nine patients with HER3-expressing cancers, of whom two expressed NRG1, received GSK2849330 (dose escalation: n = 18, dose expansion: n = 11). GSK2849330 was well tolerated. No dose-limiting toxicities were observed. The highest dose, of 30 mg/kg weekly, expected to provide full target engagement, was selected for dose expansion. Treatment-emergent adverse events (AEs) were mostly grade 1 or 2. The most common AEs were diarrhea (66%), fatigue (62%), and decreased appetite (31%). Dose-proportional plasma exposures were achieved, with evidence of HER3 inhibition in paired tissue biopsies. Of 29 patients, only 1 confirmed partial response, lasting 19 months, was noted in a patient with CD74-NRG1 -rearranged non-small cell lung cancer (NSCLC). Conclusion: GSK2849330 demonstrated a favorable safety profile, dose-proportional PK, and evidence of target engagement, but limited antitumor activity in HER3-expressing cancers. The exceptional response seen in a patient with CD74-NRG1 -rearranged NSCLC suggests further exploration in NRG1 -fusion–positive cancers. Implications for Practice: This first-in-human study confirms that GSK2849330 is well tolerated. Importantly, across a variety of HER3-expressing advanced tumors, prospective selection by HER3/NRG1 expression alone was insufficient to identify patients who could benefit from treatment with this antibody-dependent cell-mediated cytotoxicity– and complement-dependent cytotoxicity–enhanced anti-HER3 antibody. The only confirmed durable response achieved was in a patient with CD74-NRG1 -rearranged lung cancer. This highlights the potential utility of screening for NRG1 fusions prospectively across tumor types to enrich potential responders to anti-HER3 agents in ongoing trials. Abstract : This phase I, first-in-human study assessed the safety, pharmacokinetics, pharmacodynamics, and preliminary activity of GSK2849330 in patients with HER3-expressing advanced solid tumors.